Leading IT projects the IT manager's guide - Keyes, Jessica, 1950- (CRC Press, 2009)
Senior level IT managers are responsible for a wide variety of development projects. For the most part, these individual projects are handled by project managers. However, IT managers must be conversant in the field of project management. This book provides a detailed roadmap for project success.